Developing Algeria’s Tourism Sector: The Search for a Wealth-Generator - Erabti , Hana; Aimar , Abdelhafid (Finance and Business Economies Review, 2021)
Abstract: The tourism sector in Algeria is facing serious challenges and its contribution to the country’s economy is still limited, despite tremendous natural and cultural potentials, as well as an important tourism infrastructure. Indeed, Algeria is still among the bottom rankings of tourist destinations. This paper tries to put forward a number of ways to develop Algeria’s tourism sector. It seeks to make a contribution to the solution of the various problems and challenges facing the tourism industry in Algeria. It highlights the necessity of boosting domestic and foreign investment in this sector to help generate wealth and jobs to alleviate the impact of the on-going drastic decline in oil and gas prices in world markets on the national economy.